High mobility group box 1 inhibition by BoxA attenuates ovalbumin-induced allergic rhinitis in mice - Liyan Yue; Jinhui Dong; Jianxing Wang; Xiaoyan Yin; Xiumin Ren; Ou Xu; Chunguang Shan (Taylor & Francis Group, 2022)
This study was designed to evaluate the effects of BoxA on allergic rhinitis (AR). Ovalbumin (OVA)-induced AR mice model was employed and BoxA was administered to AR mice. AR symptoms, levels of cytokines and chemokines, and the expression of high mobility group box 1 (HMGB1), TLR2, and TLR4 were measured. BoxA treatment significantly ameliorated AR symptoms, decreased level of histamine, OVA-specific antibodies, suppressed the infiltration of immune cells in nasal tissues, inhibited the expression of IL-4, IL-6, IL-5, TNF-α, IL-13, IL-17, IL-2 while promoting the expression of IL-10, suppressed the expression of HMGB1, TLR2, and TLR4 in AR mice. BoxA ameliorated allergic rhinitis in mice by inhibiting HMGB1.